Nonsteroidal Anti‐inflammatory Drugs and Risk of Incident Heart Failure: A Systematic Review and Meta‐analysis of Observational Studies - Ungprasert, Patompong (Clin Cardiol, 2015)
BACKGROUND: The association between the development of heart failure (HF) and use of nonsteroidal anti‐inflammatory drugs (NSAIDs) is not well established. HYPOTHESIS: Use of NSAIDs may increase the risk of incident HF. METHODS: We conducted a systematic review and meta‐analysis of observational studies that reported odds ratio, relative risk, hazard ratio, or standardized incidence ratio comparing risk of incident HF in NSAID users vs nonusers. Pooled risk ratios (RR) and 95% confidence intervals (CI) for all NSAIDs and both subclasses (conventional NSAIDs and highly selective cyclooxygenase‐2 inhibitors [COXIBs]) were calculated using a random‐effect, generic inverse variance method. RESULTS: Seven studies with 7 543 805 participants were identified and included in our data analysis. Use of NSAIDs was associated with a significantly higher risk of developing HF, with a pooled RR of 1.17 (95% CI: 1.01‐1.36). Subgroup analysis showed a significantly elevated risk among users of conventional NSAIDs (RR: 1.35, 95% CI: 1.15‐1.57) but not users of COXIBs (RR: 1.03, 95% CI: 0.92‐1.16). CONCLUSIONS: A significantly elevated risk of incident HF was observed among users of NSAIDs.